Environmental Impact Analysis on School Building Construction in Sawangan 1 State Elementary School, Depok City - Alimuddin, Alimuddin; Agung Wahyudi, Muhammad; Heryansyah, Arien (Universitas Ibn Khaldun Bogor, 2023)
One of the goals of development is to improve the welfare of the community by building various supporting facilities and assets in people's lives. Depok City plans to build the Sawangan 1 State Elementary School. Environmental impact analysis studies are needed to predict the environmental impacts that will occur. This research aims to analysis the environmental baseline quality and predict the impacts that will occur as well as how to minimize impacts at the pre-construction stage, construction stage and operation stage. This research using observation method, interview method, and scoping. The results of this study are the initial environmental baseline at the research site indicates that the environmental quality at the research site is in good category, both in terms of ambient air quality, air quality and air quality, in order to create an environmental concept development environment. The predicted impacts that arise in the reconstruction activities of the Sawangan 1 State Elementary School, Depok City are at the pre-construction stage the impact is in the form of public perception, at the construction stage in the form of a decrease in air quality, an increase in increase, an increase in surface runoff, job opportunities and business opportunities, public health problems, domestic waste generation as well as the emergence of positive and negative public perceptions of construction activities, while at the operational stage the predicted impacts will be a decrease in air quality, increased opportunities and job opportunities for the surrounding community, public health problems, changes in environmental sanitation, traffic disturbance traffic and the emergence of public perception. In general, to minimize the negative impacts that occur in any reconstruction activity of the Sawangan 1 Elementary School building, Depok City can be carried out by means of a social approach with the community, carrying out construction activities only during the day, prioritizing local communities as workers, during the construction phase until the construction phase. and as a provider of workers' needs, optimizing reforestation in the environment and greem opem spaces as well as good waste management and complete cleaning facilities so as not to interfere with public health and produce environmentally friendly development.